3^4 .5^2 + 112 – 2^4 .7 – 5^2
3 mũ 4 . 5 mũ 2 + 112 - 2 mũ 4 . 7 -5 mũ 2
3^4 * 5^2 + 112 - 2^4 * 7 - 5^2
= 81 * 25 + 112 - 16 * 7 - 25
= 2025 + 112 - 112 - 25
= 2137 - 112 - 25
= 2025 - 25
= 2000
\(\frac{\frac{3}{7}-\frac{3}{17}+\frac{3}{37}}{\frac{5}{7}-\frac{5}{17}+\frac{5}{37}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{\frac{7}{5}-\frac{7}{4}+\frac{7}{3}-\frac{7}{2}}\) =?
\(\left(\frac{112}{13.20}+\frac{112}{20.27}+\frac{112}{37.34}+....+\frac{112}{62.69}\right):\left(\frac{5}{9.13}-\frac{7}{19.25}-\frac{13}{19.25}-\frac{31}{19.69}\right)\)=?
D=√147 +√54 -4√27
A =√112 - 7√(1/7) - 14√(1/28)-21/√7
B = 3√2(4 -√2) + 3(1 - 2√2)^2
C = 2√27 + 5√12 - 3√48
E = (√15 - 2√3)^2 + 12√5
F = 3√50 - 7√8 + 12√18
G = 2√80 - 2√245 + 2√180
H =√28 - 4√63 + 7√112
I =√44 -√176 + 2√275
cái này bấm máy tính là thầy mình k cho đâu =))) phải trình bày ra mà
D=√147 +√54 -4√27
A =√112 - 7√(1/7) - 14√(1/28)-21/√7
B = 3√2(4 -√2) + 3(1 - 2√2)^2
C = 2√27 + 5√12 - 3√48
E = (√15 - 2√3)^2 + 12√5
F = 3√50 - 7√8 + 12√18
G = 2√80 - 2√245 + 2√180
H =√28 - 4√63 + 7√112
I =√44 -√176 + 2√275
tính
14/5 -7/5=
7/8 -1/3+5/4
7/6+2/15+5/6+13/15
4/3*5/11
2/9:6*1/4
tính nhanh
3/4*4/5*5/6*6/7*7/9
22/3*1/6+1/6*2/3
9*1/3-2/5*1/3-3/5*1/3
mọi người giúp em với ạ
a: 14/5-7/5=7/5
b: 7/8-1/3+5/4
=21/24-8/24+30/24
=43/24
c; =7/6+5/6+2/15+13/15
=2+1
=3
d: =4*5/3*11=20/33
e: =2/9*1/6*1/4=2/9*1/24=1/108
2:
a: \(=\dfrac{3}{9}\cdot\dfrac{4}{4}\cdot\dfrac{5}{5}\cdot\dfrac{6}{6}\cdot\dfrac{7}{7}=\dfrac{1}{3}\)
b: \(=\dfrac{1}{6}\left(\dfrac{22}{3}-\dfrac{2}{3}\right)=\dfrac{10}{3}\cdot\dfrac{1}{6}=\dfrac{10}{18}=\dfrac{5}{9}\)
c; \(=\dfrac{1}{3}\left(9-\dfrac{2}{5}-\dfrac{3}{5}\right)=\dfrac{8}{3}\)
14/5-7/5=7/5
7/8-1/3+5/4=13/24+5/4=43/24
7/6+2/15+5/6+13/15=13/10+5/6+13/15=32/15+13/15=3
4/3*5/11=20/35
2/9:6*1/4=1/27*1/4=1/108
tính
1.\(\sqrt{147}+\sqrt{54}-4\sqrt{27}\)
2.\(\sqrt{28}-4\sqrt{63}+7\sqrt{112}\)
3.\(\sqrt{49}-5\sqrt{28}+\dfrac{1}{2}\sqrt{63}\)
4.\(\left(2\sqrt{6}-4\sqrt{3}-\dfrac{1}{4}\sqrt{8}\right).3\sqrt{6}\)
5.(\(2\sqrt{1\dfrac{9}{16}}-5\sqrt{5\dfrac{1}{16}}\)):\(\sqrt{16}\)
6.\(\left(\sqrt{48}-3\sqrt{27}-\sqrt{147}\right):\sqrt{3}\)
7.\(\left(\sqrt{50}-3\sqrt{49}\right):\sqrt{2}-\sqrt{162}:\sqrt{2}\)
8.\(\left(2\sqrt{1\dfrac{9}{10}}-\sqrt{5\dfrac{1}{10}}\right):\sqrt{10}\)
9.\(2\sqrt{\dfrac{16}{3}}-3\sqrt{\dfrac{1}{27}}-6\sqrt{\dfrac{4}{75}}\)
10.\(2\sqrt{27}-6\sqrt{\dfrac{4}{3}}+\dfrac{3}{5}\sqrt{75}\)
11.\(\dfrac{\sqrt{18}}{\sqrt{2}}-\dfrac{\sqrt{12}}{\sqrt{3}}\)
12.\(\dfrac{\sqrt{27}}{\sqrt{3}}+\dfrac{\sqrt{98}}{\sqrt{2}}-\sqrt{175}:\sqrt{7}\)
13.\(\left(\dfrac{\sqrt{8}}{\sqrt{2}}-\dfrac{\sqrt{180}}{\sqrt{5}}\right).\sqrt{5}-\sqrt{\dfrac{81}{11}}.\sqrt{11}\)
14.\(\sqrt{8\sqrt{3}}-2\sqrt{25\sqrt{12}}+4\sqrt{\sqrt{192}}\)
15.\(\left(3\sqrt{2}-2\sqrt{3}\right)\left(3\sqrt{2}+2\sqrt{3}\right)\)
16.\(\left(1+\sqrt{5}-\sqrt{3}\right)\left(1+\sqrt{5}+\sqrt{3}\right)\)
Tìm x biết
1. 2(5x-8)-3(4x-5)=4(3x-4)+11
2. (2x+1)2-(4x-1).(x-3)-15=0
3. (3x-1).(2x-7)-(1-3x).(6x-5)=0
1) \(\Rightarrow10x-16-12x+15=12x-16+11\)
\(\Rightarrow14x=4\Rightarrow x=\dfrac{2}{7}\)
2) \(\Rightarrow4x^2+4x+1-4x^2+13x-3-15=0\)
\(\Rightarrow17x=17\Rightarrow x=1\)
3) \(\Rightarrow\left(3x-1\right)\left(2x-7+6x-5\right)=0\)
\(\Rightarrow\left(2x-3\right)\left(3x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=\dfrac{1}{3}\end{matrix}\right.\)
2: Ta có: \(\left(2x+1\right)^2-\left(4x-1\right)\left(x-3\right)-15=0\)
\(\Leftrightarrow4x^2+4x+1-4x^2+12x+x-3-15=0\)
\(\Leftrightarrow17x=17\)
hay x=1
1+2-3-4+5+6-7-8+...-112-113+114
tính tổng hợp lí: a) A = -1+3-5+7-9+...-2009+2011-2013
b)B =2-4+6-8+...+2006-2008+2010
c)C =1+2-3-4+5+6-7+-8+...-111-112+113+114+115
A=2+2+...+2-2013
=2x1006+2013
=4025